(untitled) (Szociológiai Szemle, 2024)
After listing the uncertainties surrounding the preliminary measuring of intentions to emigrate, the paper — while keeping in view these uncertainties — attempts to describe those who wish to emigrate temporarily or for good. The socio-demographic characteristics, those of attitude and network, together with motivations and target countries, influencing decisions, are considered on the basis of the data of the 1994 Household Panel. The paper outlines two groups, in which migration, the planning of migration as strategy has a different meaning and conceivably the realisation of their chances are also different. The paper cannot give estimates of how many people would actually leave the country with a view of taking up jobs abroad or for good, but it helps in understanding why people seek a way out in the planning of migration.